Efficiency of different protocols for enamel clean-up after bracket debonding: an in vitro study - Lara Carvalho Freitas Sigilião; Mariana Marquezan; Carlos Nelson Elias; Antônio Carlos Ruellas; Eduardo Franzotti Sant'Anna (Dental Press Editora, 2015)
Objective: This study aimed to assess the efficiency of six protocols for cleaning-up tooth enamel after bracket debonding.Methods:A total of 60 premolars were divided into six groups, according to the tools used for clean-up: 12-blade bur at low speed (G12L), 12-blade bur at high speed (G12H), 30-blade bur at low speed (G30L), DU10CO ORTHO polisher (GDU), Renew System (GR) and Diagloss polisher (GD). Mean roughness (Ra) and mean roughness depth (Rz) of enamel surface were analyzed with a profilometer. Paired t-test was used to assess Ra and Rz before and after enamel clean-up. ANOVA/Tukey tests were used for intergroup comparison. The duration of removal procedures was recorded. The association between time and variation in enamel roughness (∆Ra, ∆Rz) were evaluated by Pearson's correlation test. Enamel topography was assessed by scanning electron microscopy (SEM).Results:In Groups G12L and G12H, original enamel roughness did not change significantly. In Groups G30L, GDU, GR and GD, a smoother surface (p < 0.05) was found after clean-up. In Groups G30L and GD, the protocols used were more time-consuming than those used in the other groups. Negative and moderate correlation was observed between time and (∆Ra, ∆Rz); Ra and (∆Ra, ∆Rz); Rz (r = - 0.445, r = - 0.475, p < 0.01).Conclusion:All enamel clean-up protocols were efficient because they did not result in increased surface roughness. The longer the time spent performing the protocol, the lower the surface roughness.